An extended γ-tubulin ring functions as a stable platform in microtubule nucleation - Erlemann, Sarah; Neuner, Annett; Gombos, Linda; Schiebel, Elmar (The journal of cell biology, 2012)
Microtubule nucleation sites in yeast consist of a ring of γ-tubulin small complexes and a slight excess of uncomplexed γ-tubulin., γ-Tubulin complexes are essential for microtubule (MT) nucleation. The γ-tubulin small complex (γ-TuSC) consists of two molecules of γ-tubulin and one molecule each of Spc97 and Spc98. In vitro, γ-TuSCs oligomerize into spirals of 13 γ-tubulin molecules per turn. However, the properties and numbers of γ-TuSCs at MT nucleation sites in vivo are unclear. In this paper, we show by fluorescence recovery after photobleaching analysis that γ-tubulin was stably integrated into MT nucleation sites and was further stabilized by tubulin binding. Importantly, tubulin showed a stronger interaction with the nucleation site than with the MT plus end, which probably provides the basis for MT nucleation. Quantitative analysis of γ-TuSCs on single MT minus ends argued for nucleation sites consisting of approximately seven γ-TuSCs with approximately three additional γ-tubulin molecules. Nucleation and anchoring of MTs required the same number of γ-tubulin molecules. We suggest that a spiral of seven γ-TuSCs with a slight surplus of γ-tubulin nucleates MTs in vivo.
Gesehen am 22.11.2018